Use of online resources at Jawaharlal Nehru University: a quantitative study. Issue 3 (1st July 2014) - Tripathi, Manorama; Kumar, Sunil
Abstract : Purpose: – The main purpose of this paper is to describe the use of e-resources at Jawaharlal Nehru University (JNU), those are being offered through the University Grant Commission – Information and Library Network (UGC-INFONET) consortium. Statistical techniques are applied on usage reports generated by e-resources vendors/publishers to understand trend and seasonality in usages of e-resources in academic libraries. The researchers evaluated gain in popularity of e-resources and drew a comparison in use of various databases of e-resources in terms of volume of downloads over a period of three years. The study would help in designing an instrument to evaluate utilization of e-resources. The cross comparison of databases helps in identifying e-resources, which have been optimally used. Design/methodology/approach: – The present study used quantitative approach to express utilization of e-resources in terms of number of downloads of full text research papers from Project Muse, Cambridge University Press, Oxford University Press, Springer Links, Taylor and Francis and JSTOR databases, accessible through the UGC-INFONET consortium. The investigation is based on secondary data of usage statistics made available by the UGC-INFONET consortium. The descriptive statistics techniques have been used in the initial phase of the investigation to understand trend in utilization of e-resources and examine robustness of various statistical tests to identify most appropriate tests for the latter phase of the investigation. The robustness analysis has been recommended for graphical and non-parametric tests for advanced investigation, in the latter phase of the study. The with-in cohort analysis techniques investigates numbers of monthly downloads from each database for a period of three years, i.e. 2008-2010 to explain seasonality in volume of downloads of e-resources. Findings: – e-Resources have been gaining popularity gradually in academic libraries; this trend is in tune with gaining of popularity of web-based intellectual resources in other sectors. The study established need of library consortium for sharing resources and subscription fee. The investigation proves significant association between numbers of downloads of e-resources from different databases in the same period; thus gain in popularity of one database encourages readers to explore other databases. The study indicates seasonality effect in the usages of e-resources in academic libraries. This seasonality effect is contemporary to the academic calendar. There are large numbers of downloads just before the examinations, which are held twice in a year and negligible number of downloads during and around long summer study breaks. Thus, the bandwidth rendered to the university is not consistently used during the academic session. The coverage of databases in terms of disciplines and numbers of journals varies to great extent. There is overlapping in the coverage of databases. The strength of students and their demands for scholarly works also vary across disciplines, thus cross comparison of numbers of downloads from databases has little meaning until impact of these three parameters are not controlled in the investigation of utilization of e-resources. Originality/value: – The literature shows that no study has been carried out for the use of e-resources by researchers of JNU.